2021
DOI: 10.1016/j.heliyon.2021.e07697
|View full text |Cite
|
Sign up to set email alerts
|

Maize (Zea mays L.) yield response to the effect of blended fertilizer and varieties under supplemental irrigation at Hadero Zuria Kebele, southern Ethiopia

Abstract: Maize is one of the staple cereal crops in Ethiopia. However, in southern Ethiopia, the productivity of the crop is very low as compared to the average national productivity, which is mainly attributed to poor soil fertility and the use of low yielding varieties. Hence, a field experiment was conducted at Hadero Zuria kebele, southern Ethiopia under supplemental irrigation to investigate the effects of different rates of blended Nitrogen, Phosphorus, Sulphur, and Boron (NPSB) fertilizer on the performance of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This may be attributed to the genetic factor that caused the variation Cultivars in trait and their response to environmental conditions. This is in agreement with [15] and [6]. It was also found that spraying 2g/L of fertilizer achieved a significant increase in (LA) that achieved (5465.47 and 5947.12 cm2) compared to the cont.…”
Section: Leaf Area (Cm 2 ) (La)supporting
confidence: 92%
“…This may be attributed to the genetic factor that caused the variation Cultivars in trait and their response to environmental conditions. This is in agreement with [15] and [6]. It was also found that spraying 2g/L of fertilizer achieved a significant increase in (LA) that achieved (5465.47 and 5947.12 cm2) compared to the cont.…”
Section: Leaf Area (Cm 2 ) (La)supporting
confidence: 92%
“…Corn is the third largest staple food in the world after wheat and rice. Increasing the productivity of corn cultivation is highly dependent on the ability to provide and apply appropriate cultivation system techniques, including the use of high-quality seeds (Bheemanahalli, Vennam, Ramamoorthy, & Reddy, 2022), spacing (Zhang, Basso, Price, Putman, & Shuai, 2018), irrigation (Kaplan, Karaman, Kardes, & Kale, 2019;Orebo, Shanka, & Hadaro, 2021), pest and disease control (Bekeko et al, 2018), and fertilizers (Sajadinia, Ghazanfari, Naghavii, Naghavi, & Tahamipur, 2021). It is important to implement these techniques to support the growth and production of corn plants by meeting their nutritional needs.…”
Section: Introductionmentioning
confidence: 99%
“…Research variables were weight measurement (g) [7]: The weight measurement was carried out by weighing the cobs that had been peeled from the cornhusk using a scale. Cob length measurement (mm) [8]: Cob length measurement was done after harvest, after the cobs are separated from the husk or peeled off. Measurements were made from the base to the tip of the cob using a tape measure or the like.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of the plant can be observed from both increases in size (length) and volume (diameter). Orebo (2021) stated that the combined treatment of nitrogen, phosphorus, sulfur and boron fertilizers (NPSB) produced a significant difference in the effect on cob length of three varieties of corn namely, 30G19, BH-546 and BH-547 [8]. The highest average cob length value of 20.79cm was obtained from the NPSB treatment of 100 kg/ha).…”
Section: Length Of Sweet Corn Cobsmentioning
confidence: 99%